2017
DOI: 10.1111/ina.12392
|View full text |Cite
|
Sign up to set email alerts
|

Human symptom responses to bioeffluents, short-chain carbonyls/acids, and long-chain carbonyls in a simulated aircraft cabin environment

Abstract: Occupants of aircraft have reported an array of symptoms related to general discomfort and irritation. Volatile organic compounds (VOCs) have been suggested to contribute to the reported symptoms. VOCs are from products used, bioeffluents from people and ozone reaction products. Thirty-six healthy, young female subjects rated symptoms and environmental quality during an 8-hour exposure to groups of compounds often present in aircraft: 1) long chain carbonyls, 2) simulated bioeffluents, and 3) short chain carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We included papers reporting measurements on aircraft under normal commercial flight conditions. We did not include studies reporting measurements in the simulated mock‐up of an aircraft 29,30 , focusing on engine emissions 31 , reporting unusual exposures during which crew members complained about cabin air quality 32 , or aimed at developing air monitoring and its applications 33 . The selected documents reported measurements published as early as in 1967.…”
Section: Review Methodologymentioning
confidence: 99%
“…We included papers reporting measurements on aircraft under normal commercial flight conditions. We did not include studies reporting measurements in the simulated mock‐up of an aircraft 29,30 , focusing on engine emissions 31 , reporting unusual exposures during which crew members complained about cabin air quality 32 , or aimed at developing air monitoring and its applications 33 . The selected documents reported measurements published as early as in 1967.…”
Section: Review Methodologymentioning
confidence: 99%
“…Measurements of cardiovascular function, microvascular oxygenation, and autonomic nervous system activity were obtained before and after 2.5 h of sitting in both conditions. Following the assessment of baseline experimental measurements, each participant sat for 2.5 h in either a control ambient environment [normal atmospheric conditions sitting (PSIT)] or in a mild hypercapnic environment (HCAP) with a CO 2 concentration of ϳ1,500 ppm, i.e., four to five times the atmospheric CO 2 concentration (32,51,95). Participants sat uninterrupted for 2.5 h to ensure that the induction of the effects of prolonged sitting, as previous studies have shown that the negative effects of prolonged sitting are induced after 1 h of sitting ( 85), but no further attenuation is observed when sitting for periods of time longer than 2 h (69).…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged periods of sitting oftentimes occur during work and leisure activities in classrooms, offices, auditoriums, etc., which have previously been identified as hypercapnic environments or having elevated levels of atmospheric carbon dioxide (CO 2 ). These densely populated and enclosed spaces tend to have a CO 2 concentration of ϳ1,500 ppm, i.e., four to five times the atmospheric CO 2 concentration (32,51,95). Although hypercapnia is involved in local blood flow (BF) regulation (72), previous studies have also reported that acute exposure to elevated CO 2 concentrations increased mean arterial pressure (MAP), heart rate (HR), cardiac output (CO), and sympathetic nerve activity (43,80).…”
Section: Introductionmentioning
confidence: 99%
“…Weisel et al 74 affirmed that some specific classes of chemicals present in aircraft cabins could contribute to the complaints reported by passengers. The complaints included not only negative perceptions of air quality but also persistent symptoms.…”
Section: State‐of‐the‐art In Cabin Air Environment Designmentioning
confidence: 99%